DEVELOPING LAB PROCEDURES FOR IoT POWER MANAGEMENT USING SLEEP MODE: AN OBE APPROACH FOR TVET EDUCATION - Zainol, Siti Maryam; Ahmad, Badlishah; Daud, Shuhaizar; Junoh, Ahmad Kadri (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
As awareness of the importance of energy efficiency in Internet of Things (IoT) systems is increasing, there is a need for educational tools that promote sustainable technology practices. In this paper, a laboratory procedure for power management using sleep mode on microcontroller-based Internet of Things devices is developed. This laboratory procedure is specifically designed for students in Technical and Vocational Education and Training (TVET) institutions studying IoT. A microcontroller, ESP32 and a temperature sensor, DHT11 are used as an IoT system that monitors temperature by sending to the cloud, Thingspeak. While another ESP32 and a current sensor, INA219, are used to measure power consumption in active, light sleep and deep sleep modes, and the current data is sent to Excel. Experimental results show that using sleep mode strategically can result in significant power savings and energy efficiency gains supported by quantitative data. A laboratory framework that is in line with the principles of Outcomes-Based Education (OBE) and the relevant Sustainable Development Goals (SDGs), specifically SDG 7 (Affordable and Clean Energy) and SDG 12 (Responsible Consumption and Production), is proposed based on these findings. Clear Course Learning Outcomes (CLOs), assessments with an emphasis on sustainability, and a CLO- Course Learning Outcomes (PLO) mapping structure that can be incorporated into current TVET curricula are all features of the lab design. This framework creates a foundation for future implementation and evaluation, despite the lack of data on student learning outcomes. This work offers a pedagogical model that promotes energy-conscious engineering education in addition to technical analysis of IoT power optimization.